High-performance humidity sensor based on plasma modified graphene. (1st October 2022) - Bai, Lin; Wang, Wenhui; Yu, Yuanfang; Liu, Kaiyang; Ni, Zhenhua
Abstract: Humidity monitoring has flourished in many advanced applications, such as environmental monitoring, industries, and medical health. Humidity devices with fast response and high sensitivity are in high demand for complicated application conditions. In this work, we bridge this gap by employing oxygen plasma treatment in a graphene-based humidity sensor. The sensitivity can be regulated from −99.2% to 153.1%, meanwhile retaining a high-speed response with rise and fall times ∼58 ms and ∼661 ms. This work provides a promising strategy for humidity detection with fast response and high sensitivity.